Unlocking the Digital Purse: Exploring Factors Influencing e-Wallet Adoption among Millennials. - Nik Mohd Zainordin, Nik Mohamad Shamim; Ismail, An Nur Nabila; Rosely, Nurhidayah; Abdullah Thani, Ayu Kamareena; Muhamad, Mira Qerul Barriah; Ahmad, Nur Azreen Farihah (International Journal of Accounting, Finance and Business, 2025)
The rapid advancement of financial technology has revolutionized payment systems in Malaysia, particularly through the widespread adoption of mobile and digital wallets. This research examines the factors influencing the adoption of e-wallets, focusing on perceived ease of use, security, social influence, and speed among millennials in Malaysia. Despite the growing popularity of e-wallets, concerns over security and uncertainties regarding adoption rates persist. Drawing on insights from a sample of 330 millennials, this study establishes a clear relationship between perceived ease of use, security, social influence, speed, and the intention to use e-wallets. The findings highlight specific concerns and preferences of millennials, a demographic pivotal in driving e-wallet usage, particularly in online transactions. To promote e-wallet adoption and work towards a cashless society, targeted strategies and interventions are necessary. Awareness campaigns must emphasize the benefits of e-wallets while addressing security concerns to instil confidence among users. Moreover, industry stakeholders can leverage these insights to enhance e-wallet systems, thus facilitating the transition towards a cashless economy. By shedding light on the factors influencing e-wallet adoption among millennials, this research contributes to the broader discourse of financial technology adoption in Malaysia. It underscores the importance of addressing user concerns and designing user-centric solutions to drive the widespread adoption of e-wallets, ultimately advancing Malaysia's journey towards a cashless society.